PEMBERDAYAAN KELOMPOK PENAMBANG TRADISIONAL MELALUI PELATIHAN PRODUKSI BATAKO RINGAN BERBASIS SISA TAMBANG DI POBOYA, KOTA PALU - Hendra Setiawan; Astri Rahayu; Nurnanigsih Nurnanigsih (Universitas Mataram, 2026)
This community service program was carried out in Poboya Village, Palu City, an area known for traditional and modern gold mining activities that generate tailing and laterite waste. These conditions have caused environmental degradation and economic dependence on unsustainable mining. The program aimed to empower traditional miners through training in lightweight brick production using mining waste, providing new technical skills and alternative eco-friendly livelihoods. The activity adopted a participatory-transformative approach consisting of five stages: socialization, technical training, application of appropriate technology, mentoring, and sustainability evaluation. The introduced technology involved a manual press mould operated by a lever system with a material composition of 50% tailing, 30% laterite, and 20% cement. The results showed significant improvement in the partners’ technical and managerial skills, the establishment of the community business group “Batako Poboya,” and increased environmental awareness and social cohesion. The group can now produce up to 100 lightweight bricks per day with an average compressive strength of 30–35 kg/cm² and has begun marketing products through social media and local building stores. This activity successfully transformed the miners’ economic behaviour from extractive to productive and sustainable. Thus, the program achieved its goal of developing a green economy empowerment model based on mining waste utilization for post-mining communities.